HUBUNGAN ANTARA TINGKAT PENDIDIKAN DENGAN KONSEPDIRI PADA WANITA INFERTIL DI RUMAH SAKIT PUTRI SURABAYA - Jaya, Pongki; Manggiasih, Vidia Atika; Andriani, Santi (Universitas Sahid Surakarta, 2015)
Fertility is a capability of a wife to be pregnant and bearing a live child by a husband that able to impregnate her. Infertile woman is one of case examples with the self-concept disorder problem. Self-concept disorders taking place may be role, body image, self-esteem and self-identity. Educational factor is very important in the constructive coping uses in problem solving. From the preliminary survey at the Putri Hospital of Surabaya obtained data that out of 8 infertile women visiting, 50% of them had the low self-concept and otherwise.The research methodology was conducted analytically by Cross Sectional approach. Sample taking used the saturated sampling/census, and there was obtained sample numbers as many as 30 respondents, and filled in questionnaire about selfconcept. Then data were analyzed by using SPS and t-test.Research results indicated that out of 30 infertile women respondents at the Obstetric and Gynecology In-Patient Room of Putri Hospital of Surabaya in 2011 indicated the existence of correlation between education level and self-concept. The higher the educational level then also the higher the self-concept had. In addition, in general respondent with self-concept that also high. Other support factors such as age, work, information and other social factors likely can influence the self-concept representation.Knowledge improvement via formal educational ladder generally needs to be improved so that created the better next generation. In the management of infertile cases it also impacted for client in the effective and constructive coping process in coping with problem solving. By understanding self-concept the client had, it is expected can facilitate the assessment process in the KIE delivery conducted both by medical and paramedical staffs psychologically.Key Words: Infertility, Educational Level, and Sel Concept